Calculating customer experience management index for telecommunication service using genetic algorithm based weighted attributes - Khan, Nusratullah; Akram, M. Usman; Shah, Asadullah; Ahmed Khan, Shoab (IEEE, 2018)
The Customers are the hearts of any industry. Telecommunication being a service oriented industry always prioritizes to find ways of making customers happy, satisfied and loyal. By recognizing this prominence, this paper presents a survey based analysis. A study is conducted to determine what makes customers of Telecommunication Industry satisfied. This paper presents a genetic algorithm (GA) based technique for assigning weights to different attributes of a service based on survey data to find overall customer experience management index (CEMI). Six attributes of service i.e. network coverage, voice call quality, drop call rate, SMS delivery, internet service and call setup duration have been considered in this research to find overall CEMI. The weights for each attribute are optimized by minimizing the error between weighted attributes based calculated CEMI and actual CEMI provided during survey process. The study has been confined within Islamabad City, the capital of Pakistan. The data is gathered through telephonic survey by calling 200 targeted customers of a mobile service provider network in Pakistan. The results indicate that network coverage, signal strength and voice quality are the major factors that highly effect the customer satisfaction. The result of this research proved that there is positive and significant relationship between dependent variables.